2014
DOI: 10.1590/0100-2945-312/13
|View full text |Cite
|
Sign up to set email alerts
|

Clonagem de canistel por estaquia

Abstract: O canistel é nativo do sul do México e América Central e seus frutos apresentam elevado teor de carotenoides e vitamina A. Sua propagação é feita via sementes, resultando em considerável variabilidade genética entre os indivíduos, sendo a propagação vegetativa preferível, a fim de fixar características desejáveis. Assim, o objetivo deste trabalho foi avaliar a propagação vegetativa por estaquia de ramos semi-herbáceos de canistel, em função de quatro genótipos e quatro concentrações de AIB. Foram utilizadas es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…These kinds of trees are classified by Colunga-García-Marín and Zizumbo-Villarreal as non-domesticated fruit trees [2]. These trees are mainly propagated by seed, but it is also possible to propagate them asexually with cuttings [3]. Mexico and Central America are considered origin centers of this species [4].…”
Section: Introductionmentioning
confidence: 99%
“…These kinds of trees are classified by Colunga-García-Marín and Zizumbo-Villarreal as non-domesticated fruit trees [2]. These trees are mainly propagated by seed, but it is also possible to propagate them asexually with cuttings [3]. Mexico and Central America are considered origin centers of this species [4].…”
Section: Introductionmentioning
confidence: 99%
“…Diversos autores reportan propagación vegetativa con éxito en especies frutales consideradas de difícil enraizamiento, por ejemplo en Citrus (De Andrade y Martins, 2003), anonas (De Figueirêdo et al, 2013;Junior y Martins, 2014), Pouteria campechiana (Chiamolera et al, 2014), Prunus salicina (Tonietto et al, 2001) e indican que la presencia de hojas en las estacas promueve la formación de raíces (Costa Junior, 2000).…”
Section: Introductionunclassified
“…Several authors reported successful vegetative propagation in fruit species considered difficult to root, for example in Citrus (De Andrade and Martins, 2003), anonas (De Figueirêdo et al, 2013, Junior and, Pouteria campechiana (Chiamolera et al, 2014) Prunus salicina (Tonietto et al, 2001) and the presence of leaves on the cuttings seams to indicate they promote the formation of roots (Costa Junior, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Pouteria campechiana (Kunt) Baehni (zapote amarillo, canistel, k´anixté), pertenece a la familia Sapotaceae, es un árbol monopodial (tipo terminalia) perennifolio con altura comúnmente de 12 a 20 m. Los frutos son cosechados cuando adquieren tonalidad amarilla (Azurdia 2005), el epicarpio es delgado y la pulpa de color amarilla, de forma ahusada o redonda con una protuberancia en la parte distal; con semillas de color café oscuro brillante, con un hilo rugoso grande en la parte ventral, con tonalidad clara (Martín & Malo 1978, Awang-Kanak & Bakar 2018. En cuanto a su cultivo, los árboles provienen de semilla y es posible la propagación asexual mediante estacas (Chiamolera et al 2014). Necesita un clima tropical o subtropical para crecer y se ha encontrado desde el nivel del mar hasta los 1,400 m snm.…”
unclassified